Pengembangan Pemberdayaan dan Demonstrasi Skill Menu “Diet Rendah Garam” pada Penderita Hipertensi - Suharno Usman; Anshar Rante; Djusmadi Rasyid (Jurnal Pengabdian Pada Masyarakat, 2021)
DEVELOPMENT OF EMPOWERMENT AND DEMONSTRATION OF “LOW SALT DIET” MENU SKILL ON PATIENTS WITH HYPERTENSION. There are 60% of people with hypertension ending in stroke, while the rest in blindness, kidney failure, and various heart diseases. JNC-8 recommends limiting high intake of salt as one of the preventions of hypertension. Public facilities or facilities especially health facilities are still minimal, health personnel are still lacking, internet access is very limited, making To'bungku village, Banggai Islands less updated on health information related to education or counseling and health empowerment training about "Low Salt Diet "Button. This activity aims to help people with hypertension to recognize and understand health education programs and low-salt diet exercises. The method used through educational training is through media leaflets, booklets, log books, and LCD projectors, demonstrations of low-salt menu cooking skills, regular meetings, and follow-up discussions. The output of this activity is an increase in community understanding and skills in selecting and preparing low-salt food ingredients. Dissemination of events in the form of scientific publication of products, booklets, and log books as other output material. Educational training activities and regular meetings by empowering participants about the management of hypertension through low salt diet interventions have a positive effect on those who are hypertensive to start implementing a low salt diet. Further involvement of health workers and family support is needed in following-up on the adoption of a low salt diet.